Association between the metabolic score for insulin resistance (METS-IR) and estimated glomerular filtration rate (eGFR) among health check-up population in Japan: A retrospective cross-sectional study - Liu, Gailing; Tao, Lin; Zhu, Qing; Jiao, Xiaojing; Yan, Lei; Shao, Fengmin (Frontiers in Endocrinology, 2022)
Aim: This study aimed to investigate the relationship between a new metric—metabolic score for insulin resistance (METS-IR)—and estimated glomerular filtration rate (eGFR) among Japanese participants who underwent health check-ups. Methods: We conducted a cross-sectional study that involved participants in a medical health screening program, which was conducted at the Medical Health Check-up Center in Japan. This retrospective study examined the relationship between METS-IR and eGFR among 881 individuals that joined the program between March 1, 2004, and December 31, 2012. Covariates consisted of serum laboratory tests and lifestyle questionnaires. Multivariate linear regression analysis was used to explore the association between METS-IR and eGFR. In addition, subgroup and interaction analyses were done based on age, sex, body mass index (BMI), alcohol use, smoking status, and hyperuricemia. Results: A total of 881 individuals participated in this study. High METS-IR was highly linked with reduced eGFR (adjusted β = -5.04, 95% confidence interval (CI): -7.65 to -2.43), while METS-IR was utilized as a categorical variable inside the multiple regression analysis. A decrease in eGFR of 2.54 units was reported for every 10-unit rise in METS-IR (adjusted β = -2.54, 95% CI: -4.04 to -1.05, P-value = 0.001). Stratified analysis suggested no marked interaction between METS-IR and eGFR across age, sex, BMI, and alcohol consumption groups. However, there was an indication of interaction between METS-IR level, smoking status (P-value = 0.001), and uric level (P-value = 0.011) on eGFR decrease. Conclusions: METS-IR is remarkably associated with eGFR among the participants who underwent health check-ups in Gifu, Japan. Although more studies are required to prove it, METS-IR could be applied as a monitoring index for early screening, primary prevention, and diagnostic and treatment management strategies for chronic kidney disease.